Cefuroxime axetil induced glossitis: a case report - Pathak, Asha; Pandey, Achyut K.; Mishra, Atul K.; Mishra, Arun K. (International Journal of Basic & Clinical Pharmacology, 2017)
Cefuroxime axetil is a semi synthetic cephalosporin antibiotic, which is prescribed for different types of infections such as lung, ear, throat, urinary tract, and skin. This is the drug of choice in the treatment and prevention of streptococcal infections. In this case, the patient was prescribed cefuroxime axetil, diclofenac, and paracetamol for pharyngitis. The patient developed glossitis 3 hrs after ingestion of above drugs which improved after withdrawing the offending drug. Glossitis is an uncommon, but serious adverse drug effect of cefuroxime axetil. It is important to recognize and manage it to prevent fatality. The case has been reported to the Pharmacovigilance Center Uttar Pradesh Rural Institute of Medical Sciences and Research Saifai, Etawah.